2019
DOI: 10.1111/padm.12569
|View full text |Cite
|
Sign up to set email alerts
|

Negative feedback, political attention, and public policy

Abstract: More than 50 years of policy research has provided evidence of negative feedback where self-correcting mechanisms reinforce stability in public policies over time. While such mechanisms are at the heart of understanding change and stability in public policies, little attention has been given to the responses of individual policymakers to public policies as a potential driver of negative feedback.Based on a unique survey dataset of spending preferences of local government politicians covering more than 90 Danis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…For instance, fruit ripening is an example of positive feedback, while 15/43 homeostasis in the human body is a traditional example of negative feedback in a closed system (Michal & Klein 2015). Negative feedback is also discussed in public policy studies (Baumgartner & Jones 2002;Bardach 2006;Zahariadis 2008;Howlett 2009) to understand how the self-correcting mechanisms can reinforce the stability of a system (Baekgaard, Larsen & Mortensen 2019).…”
Section: Cst For Rtcmentioning
confidence: 99%
“…For instance, fruit ripening is an example of positive feedback, while 15/43 homeostasis in the human body is a traditional example of negative feedback in a closed system (Michal & Klein 2015). Negative feedback is also discussed in public policy studies (Baumgartner & Jones 2002;Bardach 2006;Zahariadis 2008;Howlett 2009) to understand how the self-correcting mechanisms can reinforce the stability of a system (Baekgaard, Larsen & Mortensen 2019).…”
Section: Cst For Rtcmentioning
confidence: 99%
“…However, to account for confounders and improve the precision of our estimates we add a number of covariates in the tests using observational data. Previous research has identified these covariates as influencing preferences for spending on various policy areas for this group: gender, level of education, whether politicians are front-or backbenchers, whether they are part of the ruling mayor party, and their membership of either the powerful finance committee or the relevant standing committee (in this case the committee responsible for employment affairs) (Baekgaard 2010;Baekgaard, Larsen, and Mortensen 2019). 2 The hypotheses are tested using linear regression where municipality fixed effects are included to account for differences in conditions across municipalities such as fiscal stress, political attention, and the number of social assistance benefit recipients, while municipalitylevel cluster robust standard errors are used to account for the dependency of error terms within municipalities.…”
Section: Survey Flow and Covariatesmentioning
confidence: 99%
“…Negative feedback is often discussed in public policy studies [29][30][31][32], also as a "selfcorrecting mechanisms that reinforce stability" [33]. Also, the RTC model is based on the negative feedback for modeling the RTD.…”
Section: Envisioning Rtc In Policy Makingmentioning
confidence: 99%